'TB or not TB': the conundrum of pre-European contact tuberculosis in the Pacific. (23rd November 2020) - McDonald, S. K.; Matisoo-Smith, E. A.; Buckley, H. R.; Walter, R. K.; Aung, H. L.; Collins, C. J.; Cook, G. M.; Kardailsky, O.; Krause, J.; Knapp, M.
Abstract : Tuberculosis (TB) is a major global health threat, infecting one-third of the world's population. Despite this prominence, the age, origin and spread of the disease have been topics of contentious debate. Molecular studies suggest that Mycobacterium tuberculosis 'sensu stricto', the most common strain of TB infecting humans today, originated in Africa and from there spread into Europe and Asia. The M. tuberculosis strains most commonly found across the Pacific and the Americas today are most closely related to European strains, supporting a hypothesis that the disease only reached these regions relatively recently via European sailors or settlers. However, this hypothesis is inconsistent with palaeopathological evidence of TB-like lesions in human remains from across the Pacific that predate European contact. Similarly, genetic evidence from pre-European South American mummies challenges the notion of a European introduction of the disease into the Pacific. Here, we review the complex evidence for the age and origin of TB in the Pacific, and discuss key gaps in our knowledge and how these may be addressed. This article is part of the theme issue 'Insights into health and disease from ancient biomolecules'.